2018
DOI: 10.3389/fimmu.2018.01659
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in the Regulation of Immune Responses in the Placental Subtype of Preeclampsia

Abstract: Preeclampsia is a pregnancy-specific disorder, of which one of its major subtypes, the placental subtype is considered a response to an ischemic placental environment, impacting fetal growth and pregnancy outcome. Inflammatory immune responses have been linked to metabolic and inflammatory disorders as well as reproductive failures. In healthy pregnancy, immune regulatory mechanisms prevent excessive systemic inflammation. However, in preeclampsia, the regulation of immune responses is disrupted as a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 174 publications
(371 reference statements)
2
83
0
3
Order By: Relevance
“…29 On the other hand, active disease before and during pregnancy is associated with an increased risk of developing preeclampsia, as it has been previously reported. 32,[34][35][36][37][38][39] In fact some of these angiogenic factors are potential biomarkers for predicting preeclampsia in patients with SLE and APS, such as endoglin, sFlt-1 and PIGF, because these factors are progressively elevated in patients who are complicated with preeclampsia. 38,39 In addition, it has been found that type I interferon can generate an antiangiogenic environment, so that high levels of this cytokine may contribute to the pathogenesis of preeclampsia in some patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…29 On the other hand, active disease before and during pregnancy is associated with an increased risk of developing preeclampsia, as it has been previously reported. 32,[34][35][36][37][38][39] In fact some of these angiogenic factors are potential biomarkers for predicting preeclampsia in patients with SLE and APS, such as endoglin, sFlt-1 and PIGF, because these factors are progressively elevated in patients who are complicated with preeclampsia. 38,39 In addition, it has been found that type I interferon can generate an antiangiogenic environment, so that high levels of this cytokine may contribute to the pathogenesis of preeclampsia in some patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Activation and dysregulation of maternal immune system constitutes the second most probable mechanism of endothelial damage and dysfunction in patients with PE [ 15 , 16 ]. The activation of immune system in patients with PE leads to a proinflammatory status, including intravascular inflammation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism leading to the activation of immune cells in women with PE may be the increased shedding of syncytiotrophoblast microparticles (STBM) into maternal circulation following the increased apoptosis of trophoblast cells in the placenta [ 16 ]. Interestingly, the primary dysfunction of immune system in mother may predispose to that by negatively affecting the proper trophoblast invasion in the first half of pregnancy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[128][129][130] For instance, studies have reported decreased IL-35 and IL-9 levels and concurrent drop in CD11c+ myleloid cells and regulatory T cell populations over the course of gestation. 128 Local changes in frequencies, phenotype, and functions of immune cells in the decidua and villi have been attributed in the pathogenesis of several obstetric complications such as preterm labor, 131 PE, [132][133][134] and chorioamnionitis. 135 Indeed, first trimester placentas from women with obesity show reduced uterine NK cell numbers, which normally comprise ∼70% of the leukocyte population in early human decidua and play a central role in uterine artery remodeling and altered expression of genes in pathways associated with matrix remodeling and growth factor signaling 136 (Fig.…”
Section: Pregravid Obesity and Immune Adaptations In The Placentamentioning
confidence: 99%